EFFECT OF ZINC ADMINISTRATION TOWARD TO DIFFERENCE OF INCREASING NUTRITION STATUS ON HIV / AIDS PATIENTS - Sahadewa, Sukma (Universitas Wijaya Kusuma Surabaya, 2012)
Nutrition had the important role in patient with HIV/AIDS, it increased the immune system and delayed the progression of HIV into AIDS. Zinc played a role in optimizing immune function, especially in T cell, need for accelerating growth process, stabilized structure of cell membranes and activated growth hormone. The purpose of this study was to analyze the differences in weight and albumin levels after administration of zinc sulfate in patients with HIV/AIDS. This research is experimental research with randomized pretest posttest control group design with the provision of a double-blind treatment. Data collection techniques using questionnaire, food recall, food frequency questionnaire, anthropometry, blood sampling and laboratory examination. The results showed that there were significant differences in body weight between before and after zinc administration in the treatment group (p = 0.030), whereas in the control group showed no significant differences in body weight between before and after zinc administration (p = 0.839 ). T-test results of elevated levels of albumin difference between before and after zinc administration between the treatment and control groups showed that there were significant difference with p value = 0.673.